2017
DOI: 10.1016/j.elstat.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic charging of single granules by repeated sliding along inclined metal plates

Abstract: In this work, repeated sliding tests for single granules were investigated for their electrostatics generation. Several factors were considered including granule length-ratio, sliding face shape, sliding times, sliding area, sliding velocity, front-facing edge, plate inclined angle and humidity. Generally, it is found that electrostatics increases with granule length-ratio. Two kinds of granular sliding face shapes were used in this work, half circle and rectangle. Under the same working conditions, a granule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Another parameter that is currently not considered in charging models is the surface roughness of the colliding surfaces, which was proven to be a relevant material property for charge generation in experimental studies (Yao et al 2017;Karner et al 2014;Angus and Greber 2018). Specifically, Yao et al (2017) found that there exists a critical roughness value that maximizes the charge generated upon contact (Zhao et al 2017). Given that the surface roughness primarily affects the contact area between the two surfaces, one option to incorporate its effect on charge transfer would be to multiply the computed contact area with a surface roughness factor (may not be a constant).…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Another parameter that is currently not considered in charging models is the surface roughness of the colliding surfaces, which was proven to be a relevant material property for charge generation in experimental studies (Yao et al 2017;Karner et al 2014;Angus and Greber 2018). Specifically, Yao et al (2017) found that there exists a critical roughness value that maximizes the charge generated upon contact (Zhao et al 2017). Given that the surface roughness primarily affects the contact area between the two surfaces, one option to incorporate its effect on charge transfer would be to multiply the computed contact area with a surface roughness factor (may not be a constant).…”
Section: Surface Roughnessmentioning
confidence: 99%